Sustainability of Cancer Registration in the Kilimanjaro Region of Tanzania – A Qualitative Assessment - Zullig, Leah L. (2014)
The projected cancer burden in Africa demands a comprehensive surveillance strategy. Kilimanjaro Christian Medical Centre (KCMC) is developing a population-based cancer registry, and understanding stakeholders' perceptions of factors impacting cancer registration sustainability is critical to its long-term success. We conducted 11 semi-structured qualitative interviews with clinicians and administrators. Interviews were double-coded and evaluated for predetermined and emerging themes. Nearly half (45%) of participants discussed change commitment, stating that the cancer registry would benefit KCMC and that they were committed to it. However, change efficacy was low – participants were not confident in their shared ability to sustain the registry. Most participants (73%) discussed the importance of resource availability and administration support. Several themes emerged across interviews: (i) lack of cancer registry awareness, (ii) ambiguity about its purpose, (iii) the importance of training, (iv) the importance of outcome data, and (v) the importance of international partners. These findings may facilitate cancer registry development and sustainability in similar settings.